Optimalisasi Pengelolaan Prinsip Keuangan BUMDes: Upaya Mewujudkan Pembangunan Desa yang Berkelanjutan - didha putri; Mahirun; Putri Ayuningrum, Anggrainy (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
Abstract. One of the factors that determine village independence is being able to generate PADes. PADes is income from optimizing village potential. Referring to Law no. 6 of 2016 concerning Villages, article 72 paragraph (1) explains that village original income can come from business results, asset results, self-help and participation, mutual cooperation, and other village-original income. This study form of finding the problem that BUMDes is not yet optimal in Sumurjombalongbogo Village, Pekelongan Regency in supporting the acquisition of PADes. This study aims to identify and analyze the management principles of BUMDes in Sumurjomblangbogo Village in accordance with the Development System Dynamics Study Center and to identify and analyze the financial statements of BUMDes in Sumurjombangbogo. This research uses qualitative and quantitative descriptive analysis to obtain answers according to the objectives set. The results of this study are that the Sumurjomblangbogo BUMDes have implemented the principles of good financial management and in the coming year will realize business expansion in various business fields.